(untitled) (GEOgraphia, 2025)
It is argued that women need to be empowered in the realm of political decision–making to facilitate their real empowerment. The growing participation of women in elections is a subtle manifestation of women’s empowerment. The process of this empowerment has been gradual and not an abrupt phenomenon. Bihar is an economically backward region and male out-migration is a common phenomenon. This factor gives females in Bihar a responsibility to look after themselves and their families in the absence of male members. There is a rising trend in the voting behaviour of women in the study area but their representation is still very low. Variations in women’s participation have been observed when compared between the rural and urban areas. There is a rising trend in the voting participation of women in the study area due to several pro-women policies implemented by the ruling regime. The paper analyses the spatial variations and temporal changes in women’s electoral culture based on the findings of State Legislative Assembly Elections of 2005, 2010, 2015, and 2020. The paper is based on the qualitative research approach utilizing field survey-based narratives and secondary data available from the Election Commission of India, newspapers and reports.